Wide-angle photography : capturing landscape, portrait, street, and architectural photographs with wide-angle lenses (including tilt-shift lenses) - Marquardt, Chris (Rocky Nook, 2018)
The very thing that makes wide-angle photography so compelling also makes it a challenge: While you're sure to capture a vast scene using a wide-angle lens, it can be difficult to direct the viewer's attention when so many elements are included in an image. For many photographers, the results of their wide-angle attempts are a disappointment and they just can't seem to achieve that "Wow" they are hoping for in their images. Whether you're new to wide-angle lenses or you've been frustrated by them for a long time, expert photographer, teacher, and author Chris Marquardt is here to help. Wide-Angle Photography is packed with information--as well as beautiful and inspiring photography--that will help you take your wide-angle image making to the next level. In a friendly, accessible manner Chris walks you through in-depth discussions of both the advantages and the pitfalls of wide-angle photography, the fundamentals you need to know, composition and design principles, and the specific genres in which wide-angle lenses can be used to create outstanding images--not only for landscape photography, but for portrait, street, architectural, and interior photography, as well. Throughout the book, Chris offers hands-on exercises that drive home the concepts being taught so you can learn by doing. Chris also dedicates two full chapters to tilt-shift lenses for those who are interested in exploring and maximizing the fascinating capabilities these kinds of lenses offer. Topics include: Types of lenses and filters Understanding depth of field Angles of view, crop factors, and focal lengths Handling distortion and aberrations Composition, design, and context Point of view and perspective Wide-angle for various genres Panoramas and stitching images Tilt-shift lenses Hands-on exercises And much more ...